Pancreatopleural fistula: A rare cause of recurrent pleural effusion - Zehra Dhanani; Stephen Dachert (Respiratory Medicine Case Reports)
Pancreatopleural fistulas, rare complications of chronic pancreatitis, are often overlooked in the initial differential diagnoses of pleural effusions, resulting in delayed diagnosis and management. We present the case of an elderly male with recurrent pleural effusion and a history of chronic pancreatitis. Diagnostic challenges arose, with the initial misdiagnosis as pneumonia. Elevated pleural fluid amylase levels (11,370U/L) along with imaging findings led to the diagnosis of a pancreatopleural fistula. This case underscores the importance of considering uncommon etiologies in pleural effusions and highlights the significance of high pleural fluid amylase levels in diagnosing pancreatopleural fistulas.